2016
DOI: 10.1371/journal.pone.0167350
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Characterization of Glutamate Racemase—A New Candidate Drug Target against Burkholderia cenocepacia Infections

Abstract: The greatest obstacle for the treatment of cystic fibrosis patients infected with the Burkholderia species is their intrinsic antibiotic resistance. For this reason, there is a need to develop new effective compounds. Glutamate racemase, an essential enzyme for the biosynthesis of the bacterial cell wall, is an excellent candidate target for the design of new antibacterial drugs. To this aim, we recombinantly produced and characterized glutamate racemase from Burkholderia cenocepacia J2315. From the screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…During the last few years, we focused our attention on this topic, proposing new targets, such as the glutamate racemase (Israyilova et al, 2016), new strategies, such as the inhibition of quorum sensing (Scoffone et al, 2016;Buroni et al, 2018) and new drugs (Scoffone et al, 2014), to fight B. cenocepacia infections. We found that the benzothiadiazole derivative C109 is highly effective against B. cenocepacia (Scoffone et al, 2015) and other Gram-negative and-positive bacteria, including Mycobacterium abscessus (Hogan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…During the last few years, we focused our attention on this topic, proposing new targets, such as the glutamate racemase (Israyilova et al, 2016), new strategies, such as the inhibition of quorum sensing (Scoffone et al, 2016;Buroni et al, 2018) and new drugs (Scoffone et al, 2014), to fight B. cenocepacia infections. We found that the benzothiadiazole derivative C109 is highly effective against B. cenocepacia (Scoffone et al, 2015) and other Gram-negative and-positive bacteria, including Mycobacterium abscessus (Hogan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The DC sample was dissolved in distilled water without further sonication. The growth was determined by the resazurin method after 24 h of incubation at 37 • C; 30 µ L of resazurin solution (0.01%; Sigma Aldrich) was added to each well and the microplates were reincubated at 37 • C for about 4 h. If the color change from blue to pink, it indicated the growth of bacteria, and the minimum inhibitory concentration (MIC) was determined as the lowest concentration of the active agents that prevented this change in color [23,24].…”
Section: Antibacterial Studiesmentioning
confidence: 99%
“…All the experiments were performed thrice and DMSO was used as control. Minimum inhibitory concentration values were determined by using Resazurin microplate assay in 96 well microtitre plates [5]. For each test bacterium, density of 24 hour fresh broth culture was adjusted to 0.5 McFarland in Mueller-Hinton medium.…”
Section: Introductionmentioning
confidence: 99%